2012
DOI: 10.1089/apc.2012.0242
|View full text |Cite
|
Sign up to set email alerts
|

In-Home Mental Health Treatment for Individuals with HIV

Abstract: Mental health problems are highly prevalent among individuals with HIV and are consistently associated with negative health outcomes. However, mental illness often remains untreated due to significant psychosocial and physical barriers to treatment participation. The Collaborative HIV/AIDS Mental Health Program (CHAMP) assessed the outcomes associated with providing 9 months of in-home mental health counseling for 40 individuals with HIV and a Major Axis I mental disorder. The evidence-based Illness Management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…This finding is consistent with prior studies indicating that psychological illnesses such as PTSD are associated with worse physical health outcomes (16, 18, 44). One possible interpretation is that among PLHA, physical functioning is highly correlated with social functioning that may play a role in mediating the relationship between PTSD symptoms and physical health.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with prior studies indicating that psychological illnesses such as PTSD are associated with worse physical health outcomes (16, 18, 44). One possible interpretation is that among PLHA, physical functioning is highly correlated with social functioning that may play a role in mediating the relationship between PTSD symptoms and physical health.…”
Section: Discussionsupporting
confidence: 93%
“…18 Moreover, treating mental illness in HIV-infected populations may decrease sexual risk taking, increase prescription of antiretroviral therapy, and improve compliance with HIV treatment. [19][20][21] For these and other reasons, HIV testing is integral to the US National HIV/AIDS Strategy and test-andtreat approaches to HIV prevention. [22][23][24] An evaluation of the 1999 National Health Interview Survey (NHIS) revealed that persons with major depression episodes (including bipolar and schizoaffective disorder), generalized anxiety disorder, and panic attacks were more likely to report ever having had an HIV test than those without these disorders (45.0% vs. 31.1%).…”
mentioning
confidence: 99%
“…The remaining eight articles cover a range of types of therapy including group therapy (Quintas & Burnett, 2013), art therapy (Kapitan, Litell, & Torres, 2011) and family therapy (Mendenhall & Doherty, 2007). Five articles discuss individual therapy for adults: Reif et al (2012); Kaleeba et al (1997); Aisenberg, Dwight-Johnson, O'Brien, Ludman, and Golinelli (2012); Green, Dicks, and Buckroyd (2009); and Gray and Price (2014).…”
Section: Cbpr and Therapymentioning
confidence: 99%